Pemahaman Guru BK Tentang Pelaksanaan Layanan Peminatan pada Kurikulum 2013 - Marsetyana, Finda; Nusantoro, Eko (Indonesian Journal of Guidance and Counseling: Theory and Application, 2015)
Penelitian ini dilakukan berdasar fenomena yaitu belum adanya kesiapan tentang program peminatan di SMK Negeri se-Kota Semarang. Tujuan penelitian secara umum untuk mengetahui pemahaman guru BK tentang pelaksanaan layanan peminatan pada kurikulum 2013 di SMK Negeri se-Kota Semarang. Medote pengumpulan data yaitu angket tertutup yang diberikan kepada 44 orang guru BK SMK Negeri se Kota Semarang. Analisis data menggunakan analisis deskriptif persentase. Hasil penelitian dari Pemahaman Guru BK Tentang Pelaksanaan Layanan Peminatan Pada Kurikulum 2013 Di SMK Negeri Se-Kota Semarang termasuk dalam kategori tinggi (71.59%) dengan perincian indikator variabel yaitu pemahaman guru BK tentang kurikulum 2013 persentase sebesar 75.04% (tinggi), konsep dan strategi pelayanan bimbingan dan konseling pada kurikulum 2013 sebesar 69.31% (sedang), lingkup layanan peminatan sebesar 70.57% (tinggi), dan pelaksanaan layanan peminatan 72.22% (tinggi). Simpulan penelitian ini yakni guru BK SMK Negeri se-Kota Semarang telah mempunyai pemahaman tentang pelaksanaan layanan peminatan pada kurikulum 2013 dengan kriteria tinggi. This research was conducted based on the phenomenon that is there was no readiness about the students’ interest program vocational high schools in around Semarang.The general objective of this research was to know the counseling’s teachers deals with the implementation of students’ interest service towards the 2013 curriculum vocational high schools in around Semarang. Method of data collection is used closed questionnaire and it was given to 44 students vocational high schools in around Semarang in which the data obtained was analysed trough descriptive percentages. The research finding from counseling’s teachers about the implementation of students’ interest in the 2013 curriculum vocational high schools in around Semarang are in a high category (71.59%), with the details of the indicator variable are as follows; the understanding of counseling’s teachers abaout the 2013 curriculum which had percentage was 75.04% (high), concept and service strategy and counseling in the 2013 curriculum wa 69.31% (average), interest’s service scope was 70.57% (high), and implementation students’s interest service was 72.22% (high). By considering the study findings above, it can be concluded that the vocational high schools counseling’s teachers in around Semarang already have sufficient understanding of the implementation students’ interest service in the 2013 curriculum.